A Validation of the French Version of the Attitudes to Aging Questionnaire (AAQ): Factor Structure, Reliability and Validity. Issue 2 (22nd March 2016) - Marquet, Manon; Missotten, Pierre; Schroyen, Sarah; van Sambeek, Iris; van den Akker, Marjan; Van Den Broeke, Carine; Buntinx, Frank; Adam, Stéphane
Introduction: The Attitudes to Aging Questionnaire (AAQ) was developed to measure attitudes toward the aging process as a personal experience from the perspective of older people. The present study aimed to validate the French version of the AAQ. Participants and methods: This study examined factor structure, acceptability, reliability and validity of the AAQ's French version in 238 Belgian adults aged 60 years or older. In addition, participants provided information on demographics, self-perception of their mental and physical health (single items), quality of life (WHOQOL-OLD) and social desirability (DS-36). Results: Exploratory Factor Analysis produced a three-factor solution accounting for 36.9% of the variance. No floor or ceiling effects were found. The internal consistency, measured by Cronbach's alpha coefficients for the AAQ subscales were 0.62 (Physical Change), 0.74 (Psychological Growth), and 0.75 (Psychosocial Loss). A priori expected associations were found between AAQ subscales, self-reported health and quality of life, indicating good convergent validity. The scale also showed a good ability to discriminate between people with lower and higher education levels, supporting adequate known-groups validity. Finally, we confirmed the need to control for social desirability biases when assessing self-reported attitudes toward one's own aging. Conclusion: The data support the usefulness of the French version of the AAQ for the assessment of attitudes toward their own aging in older people.